التوافق النفسي وعلاقته بفاعلية الزات ومستوى الطموح لدى طلبة جامعة صحار بسلطنة عمان - Yahya Salim Suhail Aljabri (Universiti Sains Islam Malaysia, 2024)
The current study seeks to explore the underlying factors for psychological compatibility, self-efficacy and the ambition level, and to investigate the correlation between the dimensions of psychological compatibility from one hand, the dimensions of and self-efficacy and the ambition level from the other hand among students of Suhar University in the Sultanate of Oman.The study examined the statistical differences of the three variables attributed to gender and College.The study adopted the relational descriptive approach.The study population consisted of (5702).The study sample included (627) male and female students from Suhar University in the Sultanate of Oman. The researcher designed the study tools for the psychological compatibility mmeasure, the self-efficacy measure, and the ambition level measure.The Validity of this measure was tested through Alpha coefficient.The results of the Exploratory Factor Analysis (EFA) showed that the measures paragraphs are applied according to the theories adopted in three variables represented in psychological compatibility, self-efficacy, ambition level and each variable has a set of dimensions. The results of Multivariate Analysis of Variance (MANOVA) showed a statistically significant relationship among the personal compatibility from one hand and the effort, the effectiveness abilty from the other hand. There is no statiscally significant relationship with the initiative . As for social compatibility, the result of the analysis showed that its relationship with all dimensions of self-efficacy is statistically significant. Also there is a relationship between family compatibility with the effort and the ability of the efficiency and it is absent with the initiative. Moreover the study showed a relationship between the personal compatibility on the one hand and perseverance, endeavour, optimism and setting goals on the other hand. There is no statistically significant relationship between personal compatibility, excellence and bearing responsibility. As for social compatibility the results revealed a statistically significant relationship with all dimensions of the level of ambition. Family compatibility has achieved a statistically significant relationship with all dimensions of ambition level. As for the study of demograph variables, the results of the study showed that there are statistically significant differences attributable to gender, with personal and family compatibility, perseverance and struggle in favour of females.The results also showed that there are statistically significant differences attributed to gender in favour of males with social compatibility, ability of efficiency, excellence, bearing responsibility, optimism and setting goals.There were no statistically significant differences attributed to the gender variable in the effort and initiative.As for the college variable, the results showed that there are statistical differences for all dimensions of psychological compatibility, the dimensions of self- efficacy, optimism and goal setting attributed to the college and in favour of the Faculty of Law. In addition, there are statistical differences in perseverance and struggle in favour of the College of Arts and Education and for excellence and bearing responsibility in favour of the College of Linguistic Studies.